Development of a Pseudo-Closed Loop Solar Collector Sun Tracking System with Optimized Set-Point Paths for Flat Plate Payload - Jimoh, M. T.; Aliyu, A. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper provides the theoretical framework for the development of a pseudo-closed loop solar tracking system incorporating a microcontroller for a flat payload, where the outputs of the system (the slope and the azimuth angles of the payload) are observed and the set-points for the system are to be optimally computed by the microcontroller. It also presents, from literature, the equations and models solar angles and incident angles for the development of the optimum set point path for the tracking, and gives the outline of the signal flow plan, as well as the corresponding flowchart, for the tracking system’s components interaction. The concept would provide a cheaper and simpler alternative to dual axis solar tracking incorporating solar sensors. The models presented here are adaptable to any geographical location in Nigeria and globally.